Efektivitas Ekstrak Daun Annona Muricata Terhadap Penurunan Kolesterol Total Pada Lansia Dengan Hiperkolesterolemia Di Panti Werdha Mojopahit Mojokerto - Muhammad Al Amin; ainun najib; ali syahbana (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
The elderly experience a decrease in function, especially in the function of blood circulation. Blood circulation diseases and hormonal metabolism disorders experienced by the elderly include hypercholesterolemia. Hypercholesterolemia is a disorder of fat metabolism that triggers an increase in total blood cholesterol levels, namely> 200 mg/dl. The study aimed to determine the effectiveness of A. muricata leaf extract in decreasing total cholesterol levels in the elderly with hypercholesterolemia. Quantitative research method, using a quasi-experimental type with a group pretest-posttest design, with a sample size of 20 elderly. The sampling technique used purposive sampling, was carried out for a week consuming three times a day. The paired t-test showed a value of 8.73 and a p-value of 0.001. This study's results indicated a significant difference between the average cholesterol levels in the pre-test and post-test administration of Annona Muricata leaf extract. Compounds contained in soursop leaves, namely flavonoids, by reducing the activity of HMG-koa reductase (enzyme β-Hydroxy β-methylglutaryl-CoA) can reduce the activity of ACAT (enzyme acyl-Coa cholesterol acyltransferase), and reduce the absorption activity of cholesterol in the liver. Digestive tract. Saponin compounds in soursop leave lower cholesterol by binding to cholesterol in the intestinal lumen, thereby preventing the reabsorption of cholesterol. Saponins can bind with bile acids, which in turn will reduce the enterohepatic circulation of bile acids and cause an increase in the process of excretion of cholesterol.